Four views on the Apostle Paul - Bird, Michael F.; Schreiner, Thomas R. (Grand Rapids, MI : Zondervan, 2012)
Recent years have seen much controversy around the apostle Paul, his religious and social context, and its effects on his theology. In the helpful Counterpoints format---Four Views on the Apostle Paul, four leading scholars present their views on the best framework for describing Paul's theological perspective. --from publisher description.
Paul: a reformed reading / Thomas R. Schreiner -- The Paul of the letters: a Catholic perspective / Luke Timothy Johnson -- Christ and the church in Paul: a "post-new perspective" account / Douglas A. Campbell -- A Jewish view / Mark D. Nanos.
Includes index.
Includes bibliographical references and indexes.
Keywords: Paul, -- the Apostle, Saint